2007
DOI: 10.1029/2005ja011597
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of polar cap ionospheric patches using data assimilation

Abstract: Ionospheric F‐region patches are 2–10 larger than background electron densities in the polar ionosphere. The EISCAT Svalbard incoherent radar (ESR) observed a sequence of patches between 2000–2200 UT on 12 December 2001. In this paper the source of these structures is investigated using several other data sets, together with a convection‐driven trajectory analysis. The data are assimilated into Ionospheric Data Assimilation Three Dimensional (IDA3D). The background model used is the National Center for Atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 26 publications
3
72
1
Order By: Relevance
“…We analyzed optical images from Qaanaaq, Greenland, in the central polar cap to determine the location, extent, and motion of the patches, and then used global convection velocities from the SuperDARN network to drive a physics-based model accounting for recombination and other processes. By running the model in reverse, we were able to match the observed patches with incoherent scatter radar measurements from Sondrestrom and determine the origin of the patches to be in the afternoon sector, contrary to the findings of other recent studies suggesting that patch plasma originates from precipitation in the morning sector [MacDougall and Jayachandran, 2007;Bust and Crowley, 2007]. Another study from the active period during the autumn of 2003 was the October 30-31 "Halloween" storm.…”
Section: Other High-latitude Researchcontrasting
confidence: 47%
“…We analyzed optical images from Qaanaaq, Greenland, in the central polar cap to determine the location, extent, and motion of the patches, and then used global convection velocities from the SuperDARN network to drive a physics-based model accounting for recombination and other processes. By running the model in reverse, we were able to match the observed patches with incoherent scatter radar measurements from Sondrestrom and determine the origin of the patches to be in the afternoon sector, contrary to the findings of other recent studies suggesting that patch plasma originates from precipitation in the morning sector [MacDougall and Jayachandran, 2007;Bust and Crowley, 2007]. Another study from the active period during the autumn of 2003 was the October 30-31 "Halloween" storm.…”
Section: Other High-latitude Researchcontrasting
confidence: 47%
“…[8] Beginning from the top left of Figure 2, the International Reference Ionosphere (IRI) [Bilitza et al, 2003] is used as a background model and GPS data are used as measurements to be assimilated by Ionospheric Data Assimilation Four-Dimensional (IDA4D). IDA4D, described in 2.1, uses three-dimensional variational data assimilation to routinely produce mappings of the ionospheric densities globally .…”
Section: Methodsmentioning
confidence: 99%
“…No calculation of the ionospheric density within the flux tube is conducted. Bust and Crowley [2007] used a trajectory analysis based on maps of ionospheric convection, obtained from the assimilative Mapping of Ionospheric Electrodynamics (AMIE), to indicate that some of the patches detected by the EISCAT Svalbard radar on 12 December 2001 formed part of the TOI. Bust and Crowley's trajectory analysis demonstrated that the patches originated in several different locations either in the momingside or afternoon sectors at geographic latitudes near 60-70°.…”
Section: The Trajectory Analysis Techniquementioning
confidence: 99%
“…More recently, MacDougall and Jayachandran, [2007] used foF 2 values from several stations located in the Canadian Arctic to propose a mechanism for patch generation in which density enhancements were produced by low-energy electron precipitation as the plasma returns from midnight around the dawn convection cell. Bust and Crowley [2007] also concluded that a sequence of patches observed at Svalbard on December 12, 2001 had been transported toward noon from the morning and afternoon sectors. These authors introduced a trajectory analysis method and an assimilation scheme to demonstrate that the origin of the patch densities was at 62° geographic latitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation